Analisis Teologi-Kritis Tentang Pemali Keissinna Padang Dan Relevansinya Bagi Warga Gereja Toraja Jemaat Tambuntana - Sule Taruk Patottong; Wandrio Salewa (Jurnal Teologi Kontekstual Indonesia, 2023)
Pemali is a prohibition or taboo. One of the rituals that are still strong in Toraja society is the pemali Keissinna Padang (prohibition when plants bear fruit). This prohibition relates to not being allowed to go to the cemetery, while the rice is temporarily growing and bearing fruit in the fields. When this is violated it will cause rice plants to be damaged. The purpose of this study was to find out how the Toraja Church members of the Tambuntana congregation responded to the pemali Keissinna Padang. The research method used is qualitative research with observation and interviews and elaborated in theological-critical reflection. So from this study, it can be concluded that first, pemali Keissinna Padang is a good thing because it will regulate the order of human life so that they don't do anything arbitrary when the rice is temporarily growing in the fields. Second, pemali keissinna padang is still relevant in the lives of Toraja church members in the Tambuntana Congregation, because they always blame people who go to the graves when the rice is growing and bearing fruit. Third, this pemi is maintained as a form of mutual agreement with the whole community through the kalua'ada group (customary deliberation). Fourth, this pemi has the most basic meaning, namely love and respect for what has been agreed and done together.